Social construction in context - Gergen, Kenneth J. (SAGE, 2001)
This latest book by one the world's leading protagonists in the field will be welcomed not just by psychologists but by students, academics and professionals interested in social constructionism across a wide range of subjects. Social Construction in Context explores the potentials of social constructionist theory when placed in diverse intellectual and practical contexts.